A Speed Sensor Fault-Tolerant Control of the CPPM Machine for Electric Vehicle - Li, Zheran; Li, Yesong; Li, Xinhua (Elektronika ir Elektrotechnika, 2014)
A speed sensor fault-tolerant control (FTC) strategy for electric vehicle is proposed in electric vehicles using a consequent-pole permanent-magnet (CPPM) machine. In order to obtain good FTC performance at low speed region, a HF voltage injection method is proposed to detect the rotor position from the magnetic saliency. This magnetic saliency of a CPPM machine is analysed by the finite-element analysis (FEA), and the high-frequency (HF) impedances are measured to confirm the saliency. At high speed range, the extended-electromotive force (EMF) method is applied when the failure of the speed sensor is detected. The speed sensor FTC strategy is verified effective by experimental results on a 25kW CPPM machine at different operating conditions. The reliability is enhanced and smooth transition to the fault-tolerant operation is realized. DOI: http://dx.doi.org/10.5755/j01.eee.20.7.5087